2017
DOI: 10.1136/jclinpath-2017-204690
|View full text |Cite
|
Sign up to set email alerts
|

miR-194 as predictive biomarker of responsiveness to neoadjuvant chemoradiotherapy in patients with locally advanced rectal adenocarcinoma

Abstract: Using biopsy samples collected at diagnosis, mir-194 was significantly upregulated in patients responding to treatment (p value=0.016). The data was confirmed with qRT-PCR (p value=0.0587) and ISH (p value=0.026). Protein-protein interaction network and pathway enrichment analysis reveal a possible mechanism of susceptibility to pCRT involving Wnt pathway via its downstream mediator TRAF6. Finally, we interrogated the Comparative Toxicogenomics Database database in order to identify those chemical compounds ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 33 publications
1
24
0
1
Order By: Relevance
“…A series of 62 patients with locally advanced CRCs (all Caucasian; M/F = 42/20; age 64.3 ± 9.2 years; cTNM Stage II/III = 5/57) subjected to preoperative chemoradiotherapy followed by surgery was considered. The treatment conditions were as described in refs 32,33. All patients received a total dose of at least 45 Gy to the whole pelvis at 1.8 Gy daily, five…”
mentioning
confidence: 99%
“…A series of 62 patients with locally advanced CRCs (all Caucasian; M/F = 42/20; age 64.3 ± 9.2 years; cTNM Stage II/III = 5/57) subjected to preoperative chemoradiotherapy followed by surgery was considered. The treatment conditions were as described in refs 32,33. All patients received a total dose of at least 45 Gy to the whole pelvis at 1.8 Gy daily, five…”
mentioning
confidence: 99%
“…miRNA-194 has been described as a potential predictor of response to nCRT through a miRNA expression profiling approach combined with integrative computational biology [ 72 ]. miRNA-194 was highly expressed in endoscopic tumor biopsies collected before nCRT and before surgery that were analyzed by microarray, and then validated by RT-qPCR and in situ hybridization (ISH).…”
Section: Micrornas In Locally Advanced Rectal Cancermentioning
confidence: 99%
“…In addition, protein–protein interaction network and pathway enrichment analysis revealed that the molecular mechanism that triggers miR-194 overexpression involved the Wnt pathway via its downstream mediator tumor necrosis factor receptor-associated factor 6 (TRAF6). Moreover, the investigators suggested that the response to nCRT in which miR-194 overexpression is implicated, could be associated with the pathway of oxidative stress-induced senescence [ 72 ].…”
Section: Micrornas In Locally Advanced Rectal Cancermentioning
confidence: 99%
“…Yu et al carried out a global miRNA analysis in CRT‐sensitive and ‐resistant patients and found that miR‐345 was significantly elevated in CRT‐resistant patients ( P = 0.002) . Some other miRNAs, including miR‐194, ‐145, ‐21, ‐125b, and ‐143, have been reported to be the predictive biomarkers of CRT . None of them has been clinically assessed; however, it is possible that the optimal combination of these miRNAs can act as reliable biomarkers of a response to CRT.…”
Section: Future Of Ncrtmentioning
confidence: 99%